Pembidangan Fiqih Muamalah yang Mengarah ke Ekonomi Islam - Velany Fadia Rahma; Ahmad Mu’is; Reva Rezalita Maharani; Iknes Damayanti (Ikatan Da'i Indonesia, 2026)
Fiqh al-Mu‘āmalah is a branch of Islamic jurisprudence that discusses relationships among humans in social and economic contexts. The development of modern times and the global economic system has encouraged the emergence of Islamic economics as a practical implementation of the principles of mu‘āmalah derived from the Qur’an and the Sunnah. This article aims to analyze the classification of fiqh al-mu‘āmalah and its relevance to the development of contemporary Islamic economics. The method used is a literature review by examining both classical and modern sources related to the topic. The results of the study show that fiqh al-mu‘āmalah is divided into several main areas, such as trade (al-bay‘), partnership (syirkah), lending and borrowing (qardh), and Islamic banking, all of which serve as the foundation for the modern Islamic economic system. The implications of this research highlight the importance of integrating fiqh studies with the practice of Islamic economics to strengthen the stability and justice of the economic system within the Muslim community.Keywords: Author Guidelines; Journal Al-Kharaj; Article Templates